2013
DOI: 10.1155/2013/348212
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Glucocorticoid-Induced Apoptosis in Lymphoid Malignancies

Abstract: The initial response of lymphoid malignancies to glucocorticoids (GCs) is a critical parameter predicting successful treatment. Although being known as a strong inducer of apoptosis in lymphoid cells for almost a century, the signaling pathways regulating the susceptibility of the cells to GCs are only partly revealed. There is still a need to develop clinical tests that can predict the outcome of GC therapy. In this paper, I discuss important parameters modulating the pro-apoptotic effects of GCs, with a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 827 publications
(1,168 reference statements)
0
21
0
Order By: Relevance
“…Previously, using both microarray and deep sequencing analysis, we described the prevalent repression of annotated miRNAs during glucocorticoid-induced apoptosis of primary rat thymocytes [ 1 ]. Additional studies have demonstrated the glucocorticoid-mediated regulation of specific miRNAs in lymphoid cells, and further delineated a functional role for these miRNAs in the execution of glucocorticoid-induced apoptosis [ 30 - 33 ]. For example, studies by both Harada et al and Molitoris et al report the glucocorticoid-mediated repression of the miR-17 family, resulting in increased Bim expression, and, consequently, increased sensitivity to glucocorticoid-induced apoptosis [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, using both microarray and deep sequencing analysis, we described the prevalent repression of annotated miRNAs during glucocorticoid-induced apoptosis of primary rat thymocytes [ 1 ]. Additional studies have demonstrated the glucocorticoid-mediated regulation of specific miRNAs in lymphoid cells, and further delineated a functional role for these miRNAs in the execution of glucocorticoid-induced apoptosis [ 30 - 33 ]. For example, studies by both Harada et al and Molitoris et al report the glucocorticoid-mediated repression of the miR-17 family, resulting in increased Bim expression, and, consequently, increased sensitivity to glucocorticoid-induced apoptosis [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small, endogenous, single-strand non-coding RNAs with a length of 17-25 nucleotides (5), which exerted their function through binding to the 3' untranslated region (3' UTR) of their target mRNAs (6). Accumulating evidences have revealed that altered expression of miRNAs play an important role in tumorigenesis of many human cancers (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that up to 30-40% of patients with RCC present with metastatic disease even after radical resections [5]. Therefore, it is necessary to provide knowledge of molecule mechanisms controlling the metastatic and invasive potential of RCC.MicroRNAs (miRNAs) are a class of small and non-coding RNA molecules that regulate mRNA transcription and translation by base pairing with the 3' untranslated region (UTR) [6]. It has been well demonstrated that miRNAs are involved in the development and progression of various cancers by regulating cell proliferation, invasion, and migration [7,8].…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small and non-coding RNA molecules that regulate mRNA transcription and translation by base pairing with the 3' untranslated region (UTR) [6]. It has been well demonstrated that miRNAs are involved in the development and progression of various cancers by regulating cell proliferation, invasion, and migration [7,8].…”
mentioning
confidence: 99%